(untitled) (Research, Society and Development, 2024)
Patients frequently seek the extraction of lower third molars, primarily due to these teeth often being impacted, poorly positioned, or sources of pain and infections. Due to its close anatomical relationship with the Inferior Alveolar Nerve, this procedure carries a risk of nerve injury, such as paresthesia. This study aims to analyze the effectiveness of low-level laser therapy as a treatment for such paresthesias. An narrative literature review was conducted using the online databases PubMed and Scielo. The inclusion criteria were articles from the last 10 years that directly addressed the topic. Incomplete publications, private articles, and those not within the designated publication time frame were excluded. The data obtained were organized in a descriptive textual format. Subsequently, an analysis of the studies was performed to evaluate which articles support the treatment method in question. The authors advocate for the use of lasers as a favorable treatment option, citing their healing and tissue regeneration properties, in addition to being non-invasive. However, there is no standardized protocol for its use. Laser therapy is a viable and effective method for treating paresthesias, with the treatment protocol depending on the type, extent, and duration of the injury, and the dentist determining the appropriate approach.